Russel Effect in Indian Timber Woods - Narayanan Nambiyar, V. P. (Indian Forester, 1952)
The present paper deals with the details and results of an investigation made for the first time on the photographic activity of 40 representative specimens of Indian timber woods. Attempt is also made for the first time to measure the activity and to express it in a quantitative manner. The activity is found to be generally different for the different species of wood, though certain woods were found to exhibit the same amount of activity. Exposure to sunlight and ultra-violet light increases the activity. Extraction of the specimen with a mixture of benzene-alcohol with a view to eliminating the resinous bodies, results in an appreciable diminution in the activity of the specimen. The Russel effect exhibited by the different woods are expressed relative to teak taken as standard.The author's thanks are due to the Forest Utilization Officer, Government of Madras, through whose courtesy the specimens were procured. His thanks are also due to the authorities of the Pachaiyappa's College, Madras, for giving him all facilities to carryon the present investigation.